Planning Technical Training in Training Methods in Sambo Wrestling - Davletova Nilufar Ruzmetovna (International Journal on Integrated Education, 2022)
The fact that after the independence of Uzbekistan, the attention paid to the sport of sambo today is more important than in previous days, as evidenced by the honorable places of our athletes in the World and Asian competitions.